Editorial: engaging new analytical perspectives on gender in the African context - Sithole, Mpilo P.; Muzvidziwa, Victor N.; Ojong, Vivian B. (CSSALL Publishers, 2016)
The field of gender analysis has been marked with two conspicuous dilemmas in the course of the 20th century: a deep theoretical hype without much progress in resolving theoretical huddles in interpretation; and stagnation in gender advocacy at the political and social level. The former has meant that the main achievements at analytical level are a bit divisive with ‘womanists’ and ‘feminists’ and theorists of masculinity of various traditions of gender studies purporting different views – the divergence school of thought, the difference school of thought and the generic human rights stance. Advocacy that permeates these theoretical divergences influences the social life level and yields less substantive impacts than effort rendered. These dilemmas have, more recently, led to deeper reflection on the progress of gender analysis. Recent conferences are beginning to put the theme on gender at the centre of discussion with the view to reflect on whether the interpretations of the past century have had some constraints.